Health Care Provider Advice for African American Adults Not Meeting Health Behavior Recommendations - Elizabeth A. Fallon, PhD; Sara Wilcox, PhD; Marilyn Laken, PhD (Centers for Disease Control and Prevention, 2006)
Introduction Poor dietary habits and sedentary lifestyle contribute to excessive morbidity and mortality. Healthy People 2010 goals are for 85% of physicians to counsel their patients about physical activity and for 75% of physician office visits made by patients with cardiovascular disease, diabetes, or dyslipidemia to include dietary counseling. The purpose of this study was to 1) determine the rate of participant-reported health care provider advice for healthy lifestyle changes among African Americans who do not meet recommendations for physical activity, fruit and vegetable consumption, and healthy weight; 2) examine correlates of provider advice; and 3) assess the association between provider advice and stage of readiness for change for each of these health behaviors. Methods Data for this study were collected as part of a statewide faith-based physical activity program for African Americans. A stratified random sample of 20 African Methodist Episcopal churches in South Carolina was selected to participate in a telephone survey of members aged 18 years and older. The telephone survey, conducted over a 5-month period, asked participants a series of questions about sociodemographics, health status, physical activity, and nutrition. Analyses for moderate to vigorous physical activity, fruit and vegetable consumption, and weight loss were conducted separately. For each of these behaviors, logistic regression analyses were performed to examine the independent association of sex, age, body mass index, education, number of diagnosed diseases, perceived health, and stage of change with health care provider advice for health behaviors. Results A total of 572 church members (407 women, 165 men; mean age, 53.9 years; range, 18-102 years) completed the survey. Overall, participant-reported provider advice for lifestyle changes was 47.0% for physical activity, 38.7% for fruit and vegetable consumption, and 39.7% for weight. A greater number of diagnosed diseases and higher body mass index were independently associated with receiving advice to increase physical activity. A more advanced stage of change and a greater number of diagnosed diseases were independently associated with receiving advice for fruit and vegetable consumption. Body mass index, stage of change, and poorer perceived health were independently associated with receiving advice about weight. Conclusion Health care provider advice appears to be based predominantly on comorbidities. Because of the preventive benefit of physical activity, fruit and vegetable consumption, and healthy weight, all health care providers are urged to increase counseling for all patients not meeting health behavior recommendations.